2018
DOI: 10.1111/apm.12899
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and congenital cytomegalovirus infections in a population‐based pregnancy cohort study

Abstract: CMV is the most common cause of congenital infection. During the past few decades, there has been a change in behaviour that possibly has affected the CMV infection rate of mother and child. We investigated 1350 randomly selected pregnant women from the Norwegian Mother and Child Cohort Study using an algorithm for detection of maternal and congenital CMV (cCMV) infection including both serology and nucleic acid amplification assay. The CMV IgG seroprevalence was 54% and 23 (3.7%) mothers seroconverted. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
3
9
2
Order By: Relevance
“…Moreover, our data were also similar with results report in other world countries with values between 92.6% and 100%: Iran [22], Palestine [23], China [24], Brazil [25], Turkey [26], Nigeria [27] and Cuba [28]. In contrast, our prevalence was higher than that reported in developed countries: 42.3% in Germany [29], 46.8% in France, 49% in the United Kingdom [30], 54% in Norway [31], 56.3% in Finland [32], 58.7% in France [33], 65.9% in Italy [34], 66% in Japan [35], 62.4% in Poland [12] and 70.0% in the United States [36].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our data were also similar with results report in other world countries with values between 92.6% and 100%: Iran [22], Palestine [23], China [24], Brazil [25], Turkey [26], Nigeria [27] and Cuba [28]. In contrast, our prevalence was higher than that reported in developed countries: 42.3% in Germany [29], 46.8% in France, 49% in the United Kingdom [30], 54% in Norway [31], 56.3% in Finland [32], 58.7% in France [33], 65.9% in Italy [34], 66% in Japan [35], 62.4% in Poland [12] and 70.0% in the United States [36].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we demonstrated that the annual CMV seroconversion rates after BBFE were also approximately 3%, which was statistically not different from those with natural courses. The annual CMV seroconversion rates observed in this study were consistent with previous data obtained from pregnant women: 2.1% (24/1122) between first and third trimesters [8], 3.7% (23/621) between gestational week 17 and birth [9], and average of 2.3% in pregnancy period [10]. These results might suggest the rarity of CMV infection through the exposure events in healthcare settings.…”
Section: Discussionsupporting
confidence: 91%
“…This difference in seroprevalence remained when stratifying by age, region of origin, or year of blood sampling. A 2017 study from Norway also showed a seroprevalence of antibodies against CMV among pregnant women to be lower (54%) than what is found in our study population of mainly immigrant background (Barlinn et al 2018). A 2014 metanalysis investigating the prevalence of congenital CMV infection found that the maternal prevalence of antibodies against CMV in Africa and Asia ranged from 90% to 100%, in line with our observations (Lanzieri et al 2014).…”
Section: Cytomegalovirussupporting
confidence: 88%